An Approximation Approach to Eigenvalue Intervals for Singular Boundary Value Problems with Sign Changing and Superlinear Nonlinearities. (26th October 2009) - Lü, Haishen; Agarwal, Ravi P.; O'Regan, Donal
Abstract : This paper studies the eigenvalue interval for the singular boundary value problem− u ′′ = g ( t, u ) + λ h ( t, u ),    t ∈ ( 0, 1 ),   u ( 0 ) = 0 = u ( 1 ), whereg + h may be singular atu = 0,  t = 0, 1, and may change sign and be superlinear atu = + ∞ . The approach is based on an approximation method together with the theory of upper and lower solutions.